Effectiveness of Digital-Based Smart Math Diagram on Students' Interest and Learning Outcomes in Data and Diagram Material - Nur Mahmudah Munawwaroh; Wahyuni Suryaningtyas; Febriana Kristanti; Sandha Soemantri (Fakultas Ilmu Pendidikan Universitas PGRI Kanjuruhan Malang, 2025)
This study aims to describe the effectiveness of digital-based DIAGRAM SMART MATH on students' interest and learning outcomes in the material of data and diagrams. The type of research used is pre-experimental with a quantitative approach. The research design employs a one-group pretest-posttest. The population in this study consists of all seventh-grade students at SMP Mujahidin Surabaya. The sample was selected using purposive sampling, with a total sample of 25 students, comprising 9 males and 16 females. Data collection techniques in this study used pretests, posttests, and questionnaires. The data analysis techniques used were the One Sample T Test and N-gain. The results of the study indicate that the influence of digital-based DIAGRAM SMART MATH on the material of data and diagrams has a significant effect on students' interest and learning outcomes. This is evident from the analysis of the questionnaire used to measure students' interest, which yielded an average of 86%, falling into the very high criteria. Furthermore, the N-gain analysis results obtained a value of 0.7409, which is categorized as high. Additionally, based on the One Sample T Test analysis, the significance value obtained was 0.000 < P-value 0.05; thus, is accepted. Therefore, it can be concluded that there is an influence of digital-based DIAGRAM SMART MATH on students' interest and learning outcomes in the material of data and diagrams.